PENGARUH HIDROGEL DIAPERS TERHADAP PERTUMBUHAN BUNGA MAWAR (Rosa sp.) SEBAGAI SUMBER BELAJAR BIOLOGI BERUPA LKPD - Devi Kusumaningrum; Anak Agung Oka; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
Diaper waste containing the nutrient NPK can increase plant growth. This research aims to find out whether there is an effect of disposable diaper hydrogel on the growth of rose plants (Rosa sp.) and to find out the weight of the hydrogel which has the best effect on the growth of rose plants which is then prepared as a biology learning resource in the form of Student Worksheets. The research used a Completely Randomized Design (CRD) with 1 control and 3 treatments with 4 repetitions. The research was carried out for 2 months with the observation parameters of stem height, number of leaves, and number of petals of roses (Rosa sp.) which were analyzed using the One-Way ANOVA Test for rose plant stem height parameters and the Kruskal Wallis Test for the parameters of number of leaves and number of petals roses. The results of this research show that there is an influence of the weight of disposable diaper hydrogel on the growth of rose plants. It is known that in the analysis of stem height growth data, the calculation of Fcnt = 10.85 > F(0,05) (3,12) = 3.49. Analysis of leaf number data shows that Hcnt = 11.35 > X(0,95) (3) = 7.81. Likewise, analysis of the data on the number of petals shows that Hcnt = 10.04 > X(0,95) (3) = 7.81. The best hydrogel weight was in treatment 3 (P3) for all observed parameters. The results of this research can be used as a learning resource in the form of Student Worksheets on development and growth material in class XII plants.